Impact of gonadotropin genetic profile and ovarian reserve on controlled ovarian stimulation: data from prospective cohort of the GENOCS trial - Conforti, Alessandro; Santi, Daniele; Allegra, Adolfo; Mignini Renzini, Mario; Marino, Angelo; Brigante, Claudio; Iemmello, Roberta; Vanni, Valeria Stella; Rebecchi, Agnese; Privitera, Laura; Sperduti, Samantha; Casarini, Livio; et al. (Frontiers in Endocrinology, 2025)
IntroductionSeveral studies indicate that a specific genotype profile could influence ovarian sensitivity to exogenous gonadotropin. However, most of the previous studies were observational and retrospective and thereby more prone to bias. The aim of this study was to evaluate the impact of gonadotropin single nucleotide polymorphisms (SNPs) on the outcomes of in-vitro fertilization (IVF) in infertile patients undergoing their first ovarian stimulation (OS) cycle.MethodA multicenter, longitudinal, prospective, interventional cohort study was carried out in four clinical centers of medically assisted reproduction from August 2016 to November 2018. Only expected normo-responder women, estimated through standardized-computerized antral follicle count (AFC), stimulated with a fixed 150 IU daily dose of recombinant follicle-stimulating hormone (FSH), were included. The study population consisted of infertile normo-gonadotropic patients, aged between 34 and 39, at their first OS, with normal ovarian reserve (AFC between 8 and 16) measured with 3D automated ultrasonography and undergoing standardized OS protocol.ResultsOne hundred nineteen patients were enrolled, and the following five SNPs were studied (FSHR c.-29G>A, FSHR p.N680S, FSHB c.-211G>T, LHCGR p.S312N, and LHβ “V-LH” p.W8R). Separate and multivariate analysis of investigated polymorphisms did not show any statistical impact on the number of oocytes retrieved. However, adopting an overdominant model, heterozygosis of FSHR p.N680S SNP was associated with significantly lower duration of OS compared with homozygotic women. Considering LHCGR p.S312N polymorphism, N allele carriers required a longer duration of OS in the codominant, dominant, and log-additive models. Multivariate analysis revealed that specific genotype combinations could affect the ovarian sensitivity. A significantly higher follicle-to-oocyte index (FOI) was observed when the S or N allele of both FSHR p.N680S and LHCGR p.S312N were combined (S allele combination: difference 0.18, CI 95% 0.04–0.33, p = 0.011; N allele combination: difference 0.18, CI 95% 0.01–0.34, p = 0.037; N allele combination).DiscussionBased on our results, the combination of specific genetic variants could impact ovarian sensitivity to gonadotropin. This research adds to the controversy in the literature regarding the effect of genetic variants in IVF and ovarian response.